1978
DOI: 10.1055/s-0028-1097388
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Phenylethylamines in Plant Cell Suspension Cultures

Abstract: Cell suspension cultures of Hordeum vulgare were shown to contain N-methyltyramine, hordenine and gramine. Cell cultures of barley as well as of wheat, parsley, soybean, mungbean and chick pea degraded the phenylethylamines hordenine, tyramine and dopamine to CO,. Intermediates were N-methyltyramine and p-hydroxyphenylacetic acid, p-hydroxybenzoic acid and 3, 4dihydroxyphenylacetic acid, respectively. Oxidative polymerisation of phenylethylamines and intermediate phenols was also observed. Phenylethylamine cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 12 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…A wide variety of substituted phenethylamines have been identified in plants, including norepinephrine (3,12), tyramine (9,24), dopamine (13,19), adrenaline and dopa (1 1), N-methyl tyramine (22), and octopamine (16,26). Although these compounds have been extensively studied in insects, mollusks, and crustaceans for their neurotransmitter properties (6,18), their functions in plants remain relatively obscure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of substituted phenethylamines have been identified in plants, including norepinephrine (3,12), tyramine (9,24), dopamine (13,19), adrenaline and dopa (1 1), N-methyl tyramine (22), and octopamine (16,26). Although these compounds have been extensively studied in insects, mollusks, and crustaceans for their neurotransmitter properties (6,18), their functions in plants remain relatively obscure.…”
Section: Methodsmentioning
confidence: 99%
“…A wide variety of substituted phenethylamines have been identified in plants, including norepinephrine (3, 12), tyramine (9, 24), dopamine (13,19), adrenaline and dopa (1 1), N-methyl tyramine (22), and octopamine (16,26 Tobacco (Nicotiana tabacuum cv H425), cotton (Gossypium hirsutum cv DPL6 1), corn (Zea mays var A188), soybean (Glycine max cv Hardin, Williams, Peking, and Essex), and sunflower (Helianthus annuus L.) seeds were sterilized with commercial bleach (4-6% NaOCl) diluted 1:5 with water for 10 min, washed three times with sterile distilled water, and germinated on filter paper.…”
Section: Methodsmentioning
confidence: 99%
“…PEA and tyramine are the major monoamine constituents of tobacco and other plant tissues (Smith 1977, Slocum et al 1989. The metabolism (Endress et al 1984) and catabolism (Meyer and Barz 1978) of PEA and its derivatives seem to be similar in plants and animals. Applewhite (1973) has investigated the distribution of norepinephrine and serotonin in several so called 'action plants' and found that these two compounds are very abundant in the organs of movement, pulvini and tendrils, suggesting their role as 'plant neural transmitters'.…”
Section: Introductionmentioning
confidence: 99%
“…In view of strong N-demethylation reactions of foreign compounds previously found in cell cultures [25] further enzymatic experiments with (methyl-i4C)-nicotine will have to show whether the enzyme(s) involved are specific for nicotine. Such studies will possibly also explain the puzzling observation of incorporation of label from the methylgroup of nicotine (table I) or hordenine [25] into oligomeric and polymeric material. Such reactions have so far never been observed in 0-demethylation studies in cell cultures [26, 271 where the liberated 0-methylgroups were quantitatively oxidized to CO,.…”
Section: Discussionmentioning
confidence: 99%